Adaptive Sovereignty and Co-Evolutionary Control: State Reconfiguration in Facing Middle Eastern Methamphetamine Networks in the Indian Ocean-Southeast Asia Corridor - R. Nurhadi Yuwono; Effendy Lod Simanjutak (Jurnal Sosial Teknologi, 2026)
This research analyzes the transformation of state sovereignty in responding to co-evolutionary transnational threats, focusing on methamphetamine networks connecting the Middle East and Southeast Asia via the Indian Ocean corridor. Using the framework of Evolutionary Governance Theory (EGT) and the concept of adaptive sovereignty, this study examined a case study of the uncovering of an international network that smuggled crystal meth in coffins using a drug hardening method, as well as the practice of control delivery that led to the discovery of a methamphetamine laboratory operated by Iranian nationals. This research finds that the state no longer acts as a rigid and territorial entity, but rather as an adaptive actor capable of reconfiguring its control instruments co-evolutionarily alongside the illegal networks it faces. This case demonstrates how the meth-hardening method represents the adaptation of criminal network technology to conventional detection systems, while control delivery shows the state's capacity for policy learning by adopting the network's logic in law enforcement operations. The theoretical implications of these findings indicate that sovereignty in the contemporary era must be understood as an adaptive capacity that continuously evolves through co-evolutionary interactions with transnational actors.